1970
DOI: 10.3126/njog.v2i2.1454
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cytological study in unhealthy and healthy looking cervix

Abstract: Aim: Aim: Aim: Aim: Aim: To compare cervical cytology in women with healthy/unhealthy cervix. Methods:Methods: Methods: Methods: Methods: A prospective study on Pap smear was performed including 200 women, 100 with healthy and 100 with unhealthy cervix, attending outpatient Gynaecology clinic of the Department of Ob/Gyn TU Teaching Hospital, Kathmandu. The cytology report was compared in the two groups.Results: Results: Results: Results: Results: Cervical dysplasia was seen in 8 women with unhealthy cervix, 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
5
13
0
Order By: Relevance
“…Other studies by Kenneth et al, Khattak et al, Pradhan et al and Bal et al, found vaginal discharge as the commonest presentation. [17][18][19][20] In our present study, 74.98% of the smears showed nonspecific inflammation. Studies in populations carried out by Patel et al, Mulay et al and Bal et al have observed inflammation in smears in 19.6%, 57.48% and 74.3%, respectively.…”
Section: Discussionsupporting
confidence: 47%
“…Other studies by Kenneth et al, Khattak et al, Pradhan et al and Bal et al, found vaginal discharge as the commonest presentation. [17][18][19][20] In our present study, 74.98% of the smears showed nonspecific inflammation. Studies in populations carried out by Patel et al, Mulay et al and Bal et al have observed inflammation in smears in 19.6%, 57.48% and 74.3%, respectively.…”
Section: Discussionsupporting
confidence: 47%
“…This was in accordance with Sherwani R K et al (2007) and Khattak AT et al l (2006) in which discharge per vaginum was most common finding in 42.5% and 41 % respectively. In the study by Pradhan et al (2007) per vaginal discharge was found to be commonest complaints in different lesion of cervix however bleeding PV is found to be more specific for cervical malignancy. Our study also correlates with the above fact and signifies that PAP smear should always be done in patient with vaginal discharge as it can be a warning symptom for intraepithelial lesions.…”
Section: Resultsmentioning
confidence: 99%
“…In a study done by Pradhan 6 in 800 samples, the abnormal smears were seen mainly among age group of 21-40 years and carcinoma was also found mainly in this group. In a study done by Pradhan et al 7 in 200 samples, all of the women who had atypia, also had inflammation and were between 35 and 50 years of age, a risky age group for the development of CIN and cervical carcinoma. On analyzing 2288 Pap tests in a study done in a hospital in Nepal they had found precancerous and malignant lesions in 65 cases.…”
Section: Resultsmentioning
confidence: 99%